Deskripsi Kemampuan Guru Membuat Soal Berdasarkan Pada Kurikulum 2013 di Sekolah Menengah Atas Kabupaten Landak - Winarti Winarti; Hairida Hairida; Ira Lestari (Peneliti.net, 2021)
This study aims to describe the ability of chemistry teachers to make based on the 2013 curriculum at Landak District Senior High School. The research method used is the descriptive method. The subjects of this study were teachers at SMAN 1 Sengah Temila, SMAN 4 Sengah Temila, and SMAN 1 Menyuke. The data test tool used was to submit the results and interviews. The results of the study indicate that the teacher's ability to make questions based on the 2013 curriculum is in the sufficient category because the teacher has difficulty in making HOTS questions and the differences in the cognitive level of the questions.